PEMBAYARAN KLAIM PENJAMINAN NASABAH PENYIMPAN PADA BANK GAGAL OLEH LEMBAGA PENJAMIN SIMPANAN (Studi Putusan Mahkamah Agung Nomor 615 K/Pdt.Sus/2011) - , Fany Fadilla, Adi Sulistiyono (PRIVAT LAW II, 2016)
AbstractThis article aims to analyze the procedure for payment of depositorâs insurance claims in the failed banks by Indonesia Deposit Insurance Corporation and to analyze consideration of the judge in the case between Indonesia Deposit Insurance Corporation against curator of PT. Tripanca Group and PT. BPR Tripanca Setiadana related with payment of depositorâs insurance claims dispute. This research is a prescriptive normative legal research. The results of the study concluded that the procedure for payment of insurance claims when a bank fails started from the depositors who need to come to the office to see the announcement list of the liquidated bank deposits and requested a statement of the liquidation team. Then depositor came to the bank with the documents required and will be examined. Payerâs bank will do the payment if the savings fulfill the guarantee program. Related with Supreme Court Ruling Number 615/Pdt.Sus/2011, consideration of the Supreme Court judge granted the request of this appeal because it contains errors consideration of the Judex Facti on their decision. From Gustav Radbruch theory, the decision of the Supreme Courtâs judges have fulfill three general precepts: purposiveness, justice, and legal certainty so it can be regarded as an ideal decision.Keywords: payment of insurance claims, consideration of the judges, Deposit Insurance CorporationAbstrakArtikel ini bertujuan untuk menganalisis prosedur pembayaran klaim penjaminan nasabah penyimpan pada bank gagal oleh Lembaga Penjamin Simpanan dan menganalisis pertimbangan hakim dalam kasus antara Lembaga Penjamin Simpanan melawan Kurator PT. Tripanca Group dan PT. BPR Tripanca Setiadana terkait dengan sengketa pembayaran klaim penjaminan. Penelitian ini merupakan penelitian hukum normatif yang bersifat preskriptif. Hasil penelitian menyimpulkan bahwa prosedur pembayaran klaim penjaminan ketika bank gagal dimulai dari nasabah yang perlu datang ke kantor bank terlikuidasi untuk melihat pengumuman daftar simpanan dan meminta surat keterangan Tim Likuidasi. Nasabah kemudian mendatangi bank pembayar dengan membawa dokumen yang disyaratkan dan akan diteliti bank pembayar kemudian akan dilakukan pembayaran ketika simpanannya memenuhi program penjaminan.Terkait dengan Putusan Mahkamah Agung Nomor 615 K/Pdt.Sus/2011 Pertimbangan Majelis Hakim Mahkamah Agung mengabulkan permohonan kasasi ini adalah karena terdapat kesalahan dalam pertimbangan Judex Facti di dalam putusannya. Dilihat dari Teori Gustav Radbruch, putusan Majelis Hakim Mahkamah Agung ini telah memenuhi tiga unsur yaitu unsur keadilan, kemanfaatan dan kepastian hukum sehingga dapat dikatakan sebagai putusan yang ideal.Kata Kunci: Pembayaran klaim penjaminan, Pertimbangan Majelis Hakim, Lembaga Penjamin Simpanan.